The correlation between the styloid process length, angle, head shape, and eagle syndrome based on high-resolution CT three-dimensional reconstruction: a retrospective study - Duan, Jiaqi; Wu, Fang; Liu, Linfeng; Xu, Jianxia; Zheng, Xiaozhong; Fan, Shufeng; Rao, Qinpan (Frontiers in Medicine, 2025)
ObjectiveA comprehensive evaluation index (R value) based on the styloid process (SP) length and spatial angle orientation was constructed to explore the imaging and clinical features of Eagle Syndrome, and assess its diagnostic value in the identification of Eagle Syndrome.MethodsA retrospective analysis was conducted on the high-resolution CT (HRCT) three-dimensional reconstruction maximum intensity projection (MIP), with a data of 57 clinically diagnosed Eagle Syndrome (ES group) and 49 Non Eagle Syndrome (NES group). The bilateral SP length, inward angulation, and forward tilt angle were measured. A comprehensive evaluation index, the R value, was introduced based on the head shape. Independent two-sample t-tests were used to compare the differences in parameters between the two groups, and ROC curve analysis was performed to assess the diagnostic efficacy of the R value. Finally, binary logistic regression was employed to validate the stability of the model.ResultsThe ES Group exhibited significantly higher parameters compared to the NES Group in terms of SP length (left: 34.19 ± 5.14 mm, right: 34.13 ± 6.40 mm), inward angulation (left: 24.29° ± 3.09°, right: 22.22° ± 3.18°), and forward tilt angle (left: 28.39 ± 2.76°, right: 28.29 ± 2.72°). The ROC curve analysis of the R value showed that the left side had a AUC of 0.86 (95% CI, 0.79–0.93), with an optimal cutoff value of 2.85, sensitivity of 82.5%, and specificity of 79.6%. The right side had an AUC of 0.82 (95% CI, 0.74–0.90), with an optimal cutoff value of 2.72, sensitivity of 78.9%, and specificity of 75.5%. The binary logistic regression results demonstrated that the R value exhibits excellent discriminative ability in the diagnosis of Eagle Syndrome. In particular, when the left R > 2.85 and/or right R > 2.72, Eagle Syndrome should be strongly suspected, and a precise diagnosis should be made in combination with clinical symptoms.ConclusionEagle Syndrome is closely related to the length and angle of the SP. The R value, as a composite evaluation index integrating key anatomical parameters such as length and angle, demonstrates high diagnostic efficacy and significant clinical utility. Moreover, R value (The left R > 2.85 and/or right R > 2.72) can be applied as quantitative reference criteria for diagnosis.